DEBATING MIGRANTS IN KOREAN MULTICULTURALISM - Burhan, Ph.D, Amelia (UI Scholars Hub, 2024)
The concept of multiculturalism has become a keyword of contemporary Korean society. The influx of migrants has made Korea could not escape becoming an ethnically diverse nation and a multicultural society. This study aims to understand the concept of Korean multiculturalism through migrant workers and marriage migrants by examining their life in Korea including what kind of issues the migrants have been encountered and how was the effort of Korean government in tackling those issues. It found that the government occupied an important position in leading multiculturalism in Korea as it was the one who promoted Korea's moving towards multiculturalism particularly by leading migrants coming into Korea. Indeed, the incoming of migrants has diversied Korea's homogenous culture, but migrants seemed to only serve as a